2015
DOI: 10.1002/app.42330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of convergent–divergent flow on thermal and crystallization properties of PP/MWCNTs nanocomposites

Abstract: A melt-mixing process based on convergent-divergent flow has been used to prepare PP/MWCNT composites with a selfbuilt convergent-divergent die (C-D die) composed of different numbers of convergent plates. Dynamic extensional deformation was generated in the C-D die, which improved the mixing effect and mixing efficiency of the composites during extrusion. The C-D die acted as a mixer for composites when mounted onto a capillary rheometer. The residence time of PP/MWCNTs melt in the extensional flow field is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The mixing unit is composed of a mixing stator, one long vane and part of the rotor. The structure and working principle of the feeding unit and the mixing unit were introduced in detail in our previous studies . The feeding unit and the mixing unit are connected with a baffle.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…The mixing unit is composed of a mixing stator, one long vane and part of the rotor. The structure and working principle of the feeding unit and the mixing unit were introduced in detail in our previous studies . The feeding unit and the mixing unit are connected with a baffle.…”
Section: Methodssupporting
confidence: 93%
“…As shown in Figs and , the materials suffer dynamic elongation stress generated by the periodically changing volume of the mixing chamber which is expected to contribute significantly to dispersive mixing. These results are in accordance with those of our earlier studies . From Figs (a) and (b), individual CNTs can be found in the matrix with few entangled CNT clusters when the CNT loading is low.…”
Section: Resultsmentioning
confidence: 76%
“…Unique mixing devices that generate extensional flows along the extrusion direction can improve the dispersion state by decreasing the contraction ratio in C-D geometry [6] and increasing the flow rate and number of extensional flows or residence time. [7][8][9][10] However, few studies have focused on generating extensional flow inside the barrel of a TSE by modifying the geometry of the element because these mixing devices are add-on units to the outlet of extruders or stand-alone devices.…”
Section: Introductionmentioning
confidence: 99%
“…capillary die and hyperbolic die) on the mixing and properties of polymer or polymer‐based composites, suggesting that elongational flow afforded not only the good dispersion or exfoliation of fillers but also the orientation of macromolecular chains and fillers, which improved the mechanical properties. We previously reported that elongational flow provided uniform dispersion of immiscible blends that exhibited good mech0061nical properties …”
Section: Introductionmentioning
confidence: 99%